DESIGN OF SALES PROCEDURE MONITORING SYSTEM AS THE BASIS OF DEVELOPING THE 'BERNADY LAND' DIGITALIZATION APPLICATION - Siti Maria Wardayati; Wasito Wasito; Alfi Arif; Septarina Prita Dania Sofianti; Nining Ika Wahyuni; Marieta Julianti (UNEJ e-Proceeding, 2022)
The purpose of this service community program is to design monitoring system of sales procedure as the basis of the 'Bernady Land' marketing digitalization application. This community services planning program include of conducting a field survey, designing sales system, and monitoring the system that has been alreasy used. Social media marketing and customer service automation are used as digital marketing strategy. This community service took placed in PT Ika Setia Agung Pratama which is located at Jl. Cendrawasih, Slawu, Kec. Patrang, Jember Regency, East Java 68116. PT Ika Setia Agung Pratama was clasified as company in the property sector. This community service program will be held for 90 days starts from February to May 2022. The First Month Community Service Activities are field surveys and design of sales systems and procedures. The second and third months of monitoring the implementation of sales systems and procedures as the basis for preparing digital marketing applications. The output of the service program are marketing digitalization application system's manual and an improvement in the internal control system of sales procedures. Keywords: Digitalization of Marketing, Social Media Marketing, Customer Service Automation